Desenvolvimento de um modelo de cuidado baseado na atenção primária à saúde - Cibeira, Gabriela Herrmann (Universidade do Vale do Rio dos Sinos, 2020)
It is necessary to develop innovative Health Care Models which help industries to carry out the health management of their employees more effectively. In this context, the use of structured Research, Development and Innovation processes in companies combined with Project Management methods can support initiatives for the development of new portfolio services. Therefore, the aim of this work is to describe the implementation of a new model of Health Management, based on the principles of Primary Health Care. The proposed model was developed based on listening workshops accomplished with industries in the state of Rio Grande do Sul and validated with a bibliographic search. The Model was tested in a large company from the mechanical metal segment, located in the great Porto Alegre. As a result, it was observed that 35% of workers had high blood pressure, which was defined as the priority line of care to be implemented. In addition, only 1.8% was referred to the specialist, reinforcing the effectiveness of the implemented program. It is concluded that the Model was effective, although still in progress. It is reinforced that the process of designing new services, especially those focused on health, must be carried out together with the client, aiming to achieve greater assertiveness.
Keywords: Atenção primária à saúde; Inovação; Pesquisa e Desenvolvimento; Saúde; Primary health care; Innovation; Research and Development; Health